Late orogenic tectonics in the Ligurian Alps (Italy): constraints from syntectonic sedimentary deposits at the top of an exhumed plate interface. Issue 2 (1st December 2022) - Federico, Laura; Crispini, Laura; Scarsi, Marco; Capponi, Giovanni; Piazza, Michele
ABSTRACT: This new map at 1:25, 000 scale covers an area in the Western Alps (Italy), where the HP metamorphic basement is covered by a (predominantly clastic) late- and post-orogenic upper Eocene-lower Miocene cover. This provides unequivocal evidence that exhumation of the metamorphic units was accomplished by the lower Oligocene. The basement is made up of tectonic units with different metamorphic peaks that coupled during the exhumation path. Both basement and cover are affected by long-wavelength, asymmetric folds and thrust faults with top-to-E-NE vergence; this deformation phase has long been interpreted as linked to the rotation of the Corsica-Sardinia block and contemporary opening of the Liguro-Balearic basin and beginning of the Apennine orogeny. We particularly investigated some of these structures that crop out in the mapped area to give further constraints on their distribution, type and kinematics and to frame them in a larger picture of left-hand strike-slip tectonics.